2012
DOI: 10.1177/1076029612464900
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Assist Device–Induced Coagulation and Platelet Activation and Effect of the Current Anticoagulant Therapy Regimen

Abstract: Left ventricular assist devices (LVADs) are mechanical pumps that enhance cardiac function in patients with heart failure. In all, 7 patients with an LVADs (1.8 international normalized ratio warfarin, 81 mg aspirin) were evaluated monthly for 3 months for platelet and coagulation activation (controls: 5 healthy adults and 5 patients having warfarin). Platelet works revealed greater inhibition of collagen (31.8% vs 7.9%; P = .004), arachidonate- (30.9% vs 8.2%; P = .001), and adenosine diphosphate- (10.9% vs 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Regarding implanted-patients with HM-II or HM-III, we also observed a normal VWF propeptide/VWF:Ag ratio as previously described after LVAD implantation. 22…”
Section: Resultsmentioning
confidence: 99%
“…Regarding implanted-patients with HM-II or HM-III, we also observed a normal VWF propeptide/VWF:Ag ratio as previously described after LVAD implantation. 22…”
Section: Resultsmentioning
confidence: 99%
“…16 Similar lack of platelet biomarker expression was also observed in patients supported with the HeartMate II LVAD – independent of length of LVAD support, patient age, or antiplatelet regiment. 17, 18 …”
Section: Platelet Activation and Lvadsmentioning
confidence: 99%
“…Once MAC is initiated, blood is constantly exposed to device artificial surfaces and blood cells experience non-physiological shear stress (NPSS) from the pump. The high-speed impeller rotation of a rotary pump generates high NPSS in certain regions, such as blade-tip gap and the impeller passage, which is often above 100 Pascal (Pa) and sometimes higher than 600 Pa. 9 It is well known that NPSS causes damage to blood cells and plasma proteins, including hemolysis, 10 platelet activation and receptor shedding, [11][12][13] degradation of von Willebrand factor (vWF), 14,15 and deleterious alterations of leukocytes. 16,17 One in vitro study even suggested that leukocytes were more vulnerable to mechanical trauma than red blood cells (RBCs).…”
Section: Introductionmentioning
confidence: 99%